2018
DOI: 10.1002/jbio.201800245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone healing following Er:YAG laser ablation in rat calvaria compared with bur drilling

Abstract: The Er:YAG laser is currently used for bone ablation. However, the effect of Er:YAG laser irradiation on bone healing remains unclear. The aim of this study was to investigate bone healing following ablation by laser irradiation as compared with bur drilling. Rat calvarial bone was ablated using Er:YAG laser or bur with water coolant. Er:YAG laser effectively ablated bone without major thermal changes. In vivo micro‐computed tomography analysis revealed that laser irradiation showed significantly higher bone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…This result is associated with the promoted calcification of osteoblasts by Er:YAG laser irradiation. We also reported that Bglap expression was significantly increased in the granulation tissues of Er:YAG laser-ablated bone defects compared to that of bur-drilled bone defects at 1 week after treatment in rat (Ohsugi et al, 2019). A previous study reported that mineralization of rat calvarial osteoblasts was initiated when cultured in osteogenic induction medium for 3 days, which was earlier than that of mouse osteoblasts on FIGURE 6 | qPCR analysis of mRNA expression in osteoblast-like cells irradiated by low-level Er:YAG laser.…”
Section: Discussionmentioning
confidence: 67%
“…This result is associated with the promoted calcification of osteoblasts by Er:YAG laser irradiation. We also reported that Bglap expression was significantly increased in the granulation tissues of Er:YAG laser-ablated bone defects compared to that of bur-drilled bone defects at 1 week after treatment in rat (Ohsugi et al, 2019). A previous study reported that mineralization of rat calvarial osteoblasts was initiated when cultured in osteogenic induction medium for 3 days, which was earlier than that of mouse osteoblasts on FIGURE 6 | qPCR analysis of mRNA expression in osteoblast-like cells irradiated by low-level Er:YAG laser.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, the increase of inflammation-related genes might be the evidence of suppressed new bone formation in the bur-drilled bone compared to the laser-ablated bone, as reported previously. 17 Furthermore, Hippo signaling pathway was significantly enriched in the laser-ablated bone compared to that of the untreated control bone at 6 hours, although no significant enrichment of the pathway was observed in the bur-drilled bone. Mechanical stress suppresses Sost expression in bone.…”
Section: Discussionmentioning
confidence: 88%
“…Then, serial frontal sections were stained with hematoxylin and eosin, as previously described. 17 The distance from the treated bone surface to the empty lacuna was measured.…”
Section: Histological and Immunohistochemical Analysismentioning
confidence: 99%
See 2 more Smart Citations